Potensi Bawang Merah (Allium Cepa L. Var. Aggregatum) sebagai Imunomodulator dan Agen Antikanker: A Literature Review - Sunniyyah Farah Tsaabitah (STIKES Columbia Asia Medan, 2025)
Shallot (Allium cepa L. var. aggregatum) is a horticultural plant that holds significant economic value and therapeutic potential. This study aims to examine the potential of shallots as an immunomodulatory and anticancer agent based on a literature review of various experimental studies. The main bioactive compounds in shallots, such as quercetin, flavonoids, saponins, and sulfur-containing compounds, have been shown to modulate the immune system and inhibit cancer cell growth. As an immunomodulator, shallot extracts have been found to enhance phagocytic activity, stimulate immune cell proliferation, and balance the Th1/Th2 immune response. On the other hand, its anticancer activity is realized through cell cycle inhibition, apoptosis induction, and cytotoxic effects on various cancer cell types, including breast, colorectal, and prostate cancer. This review was conducted by analyzing experimental in vitro and in vivo studies published between 2014 and 2024. The synthesis results indicate that shallots hold strong potential as a supportive therapy for immune-related diseases and cancer. However, further clinical trials and toxicological studies are needed to confirm their efficacy and safety as a natural-based therapeutic agent.